DIDACTIC POSSIBILITIES OF DIGITAL EDUCATIONAL RESOURCES IN TEACHING A FOREIGN LANGUAGE - Sagynbay, А.А. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2022)
The article reveals the importance and application of electronic educational resources in teaching a foreign language and a unique opportunity for learners to use authentic texts, listen and communicate with native speakers to create a natural language environment. The article presents an idea of the theoretical model of electronic educational resources that makes it possible to use a huge number of additional materials that allow you to enrich foreign language lessons with a variety of exercises, making it more productive, creative and interesting.
Keywords: digital educational resources; teaching foreign language; the internet